The mystical and physical splendour of Tayeb Salih’s ‘the wedding of Zein’ - Adeyemo, Lateef Kayode; Zekrgoo, Amir Hossein (Akademi Seni, Buhaya & Warisan Kebangsan, 2013)
Sufism (Islamic Mysticism) depicts different things to different scholars including Muslim mystics themselves. It is even argued by some western scholars (orientalists) that one can be a mystic without adhering to any religion at all . Hence, it is asserted that no basis of mysticism exists unless some such relationship between the human soul and God is pre-supposed… Islamic Mysticism is, however, considered by some Muslim scholars as a higher level of religious vocation or practice, while it is considered a complete aberration by others. We have, against this background, look at the mystical and physical beauty of “The Wedding of Zein.” Zein was a rare and very strange personage of mystical and mysterious idiosyncrasies and temperament, much as the events and happenings in his life were strange and mystical. However, more important is the mystical feat and flair exhibited by NiÑmah, a beautiful lady sought after by all the young and old men of the village, which made their marriage a huge success. She was drowned in the ocean of her mystical thought, so much so that she no longer belonged to the realm of mortals but found a dwelling place for herself in the spiritual realm of the celestial habitat, for unless she did this, their marriage could never have come to pass. The marriage was, no doubt, one of the great wonders witnessed by the villagers in their respective and collective lives owing to its spiritual splendour and mystical colourations.